2008
DOI: 10.3382/ps.2007-00296
|View full text |Cite
|
Sign up to set email alerts
|

Role of Calpains in Postmortem Proteolysis in Chicken Muscle

Abstract: Tenderness is governed by postmortem biochemical processes, particularly proteolysis. In mammals, the calpain system is generally accepted as the main system involved in postmortem proteolysis. In poultry, the 2 calpains (mu and mu/m--a form only found in bird tissue) have greater calcium sensitivity. In this study, we quantified by zymography the changes in postmortem calpain system activity. The mu/m-calpain activity remained steady, whereas the mu-calpain activity had disappeared by 6 h after postmortem, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 49 publications
10
56
0
1
Order By: Relevance
“…Namely, Tmod is a dynamic cap, and the injury imposed on the muscle tissue by the biopsy excision procedure may lead to calpain-mediated proteolysis of myofibrillar components (15,16,31), including Tmod, followed by Tmod dissociation from the thin-filament pointed ends. This can potentially lead to actin monomer addition and artifactually increased thin-filament lengths.…”
Section: Biomechanical Implications Of Thin-filament Length Heterogenmentioning
confidence: 99%
“…Namely, Tmod is a dynamic cap, and the injury imposed on the muscle tissue by the biopsy excision procedure may lead to calpain-mediated proteolysis of myofibrillar components (15,16,31), including Tmod, followed by Tmod dissociation from the thin-filament pointed ends. This can potentially lead to actin monomer addition and artifactually increased thin-filament lengths.…”
Section: Biomechanical Implications Of Thin-filament Length Heterogenmentioning
confidence: 99%
“…The increase in solubility of total proteins during storage could be due to the proteolytic activities resulting in shorter peptides and free amino acids (Azad & Akter, 2005;Montero, GÓ Mez-guille´n, & Borderias, 1996;Zhang, Farouk, Young, Weliczko, & Podmore, 2005). It is generally accepted that proteolysis of the myofibrillar structure is an important factor in protein solubility and meat tenderness and that 90% or more of the observed proteolytic activity during the first 7-10 days of postmortem storage at 2-48C can be attributed to the calpains (Lee, Sante´-Lhoutellier, Vigouroux, Briand, & Briand, 2008;Sazili, Parr, Sensky, Jones, Bardsley, & Buttery, 2005).…”
Section: Nsimentioning
confidence: 99%
“…Similar values were reported by Young et al (1999) that had found pH 6.19 after deboning and pH 5.96 to 6.08 for deboning times of 2 to 6 hours. Lee et al (2008) found a decrease in pH from zero to 6 hours, time which the muscle had reached its final pH (rigor mortis). Thielke et al (2005) observed pH decrease during the first 5 hours of aging, 6.83 to 5.91.…”
Section: Raw Materialsmentioning
confidence: 95%
“…Ageing is an alternative to reduce these problems, consisting in exposing the meat to controlled temperature (0 to 4°C) for a determined period of time (6 to 24 hours) (KOMIYAMA et al, 2009;LIU et al, 2004;LEE et al, 2008). The ageing time before deboning is one of the most important factors for the final texture of the meat (SOUZA et al, 2005).…”
Section: Introductionmentioning
confidence: 99%